Gust rejection in multirotor aircraft using sliding mode control - Shaik, Mukarram Khasimul (Cranfield University, 2023)
Multirotor aircraft are being used in many applications because of their mechanical simplicity and high manoeuvrability. Many potential applications of multirotor aircraft are in gusty and turbulent environ- ments, it is imperative for them to have a stable hovering as well as offer resistance to transient gusts and winds. Many research studies have been carried out with regards to control of the multirotor aircraft but not much work has been undertaken considering the aerodynamic effects impacting the aircraft, in particular the rotor tilt angle. As the Vertical Take Off and Landing (VTOL) aircrafts are light-weight, they are prone to gusty wind conditions and desired landing and hovering is a great challenge during these disturbances. In this research work, an analysis of the effect of rotor tilt on the stability and gust rejection properties is performed with a conceptual planar birotor initially and then extended to quadrotors. The gust rejection properties of multirotor aircraft are also examined using sliding mode control taking rotor tilt angle into account. Models of the aircraft were developed in MATLAB/Simulink to implement nonlinear dynamic equations of the multirotor vehicles. A range of rotor tilt angles have been considered and investigated for gust rejection through extensive simulation studies using Proportional-Integral-Velocity (PIV) control, Sliding Mode Control (SMC) of altitude, attitude and PIV position control and a complete SMC control of altitude, attitude and position control. The performance of the three controllers were compared through numerical simulations. It was found that the complete sliding mode controller is very robust at rejecting the gust and shows that the rotor tilt angle does not impact on the vehicle stability when used with SMC, even in the presence of parametric uncertainties and external disturbances. Finally, suggestions for further work based on this research are presented on further design and development of sliding mode controllers for di erent multirotor con gurations.
Keywords: rotor tilt angle; conceptual planar birotor; quadrotors; Proportional-Integral-Velocity (PIV); Sliding Mode Control (SMC); altitude